Peningkatan Kapasitas Aparatur Kampung Dalam Melaksanakan Tugas Administrasi Kampung Urumb Distrik Semangga Kabupaten Merauke - Fransin Kontu; Umiyati Haris; Syahrabudin Husein Enala; Hubertus Oja; Nurkholis Syukron (Politeknik Kampar, 2023)
This community service aims to increase the capacity of village officials in carrying out administrative tasks in Urumb Village, Semangga District, Merauke Regency. Capacity building of village officials is essential in ensuring efficient and quality public services to the local community. The approach in this community service involves collaboration between the research team and village officials. In this activity, two days of socialization and training were conducted. In the process, the authors used participatory methods that actively involved village officials in the planning and implementation of the program. The results of this community service showed positive changes in the capacity of village officials in administrative tasks. There was a significant increase in their understanding of the functions and authority of village government administration as well as the types and forms of village government administration. Some success factors that encourage positive results in this community service are: support from the village government; active involvement of village officials; and good communication between researchers and village officials. This community service makes a real contribution in increasing the capacity of village officials in village administration tasks. The results create a stronger foundation for better governance and more efficient public services in Urumb Village, Semangga District. It is recommended that this collaborative approach can be applied in other villages to improve administrative capacity across the region.